(untitled) (Plant Bulletin, 2025)
Over half of the world’s population consumes rice, which is commonly grown in Asia by transplanting. The labour, water, and energy demand drive this production system, which has become less profitable as these resources become limited. Rice is a heavily irrigated crop in Asia, and saving water in rice cultivation systems has long been a priority of agricultural research. As worldwide water demand rises, aerobic or dry-seeded rice (DSR) irrigation with alternating wetting and drying (AWD) has become a viable water-saving method for rice cultivation. The DSR and AWD are gaining traction in several Asian nations by addressing water and labour constraints and improving system sustainability. The DSR and AWD strategies are beneficial in lowering water consumption, methane emissions, and production costs, resulting in increased productivity and profitability. However, DSR and AWD use in Pakistan is not prevalent due to policy implications, including educating farmers on the benefits of DSR and AWD and promoting the broader use of water-saving techniques. Therefore, the study aimed to screen the rice lines against DSR and AWD techniques to promote these technologies. The results showed that all rice lines performed well under DSR and AWD. Using these techniques, water savings ranged from 25–32%, along with a 14% increase in production. The study recommends that the AWD 15 be used in farmer’s fields to increase productivity while maintaining quality. In conclusion, the research suggested that farmers use both strategies to save on inputs while increasing profits.